1998
DOI: 10.1021/ja981549p
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Nature of Water Bound to Solid Acid Surfaces. Ab Initio Simulation on HSAPO-34

Abstract: Ab initio simulations of water adsorbed in the microporous silicoaluminum phosphate HSAPO-34 are reported. A neutron diffraction study by L. Smith et al., Science 1996, 271, 799, showed that both H2O and H3O+ are present when this solid acid is loaded with water. The ab initio simulations support this; however, new details are revealed which are not accessible by diffraction experiments averaging over all sites. The acid−base reaction requires at least three water molecules per two nearby acidic sites in the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
98
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 89 publications
(111 citation statements)
references
References 22 publications
12
98
0
1
Order By: Relevance
“…For water, which has a lower proton affinity than methanol (697 kJ/mol vs 761 kJ/mol [77] ), higher loadings are required to obtain similar levels of proton transfer. With sufficient amounts of water, hydronium ions can be stable species, which is in correspondence with the findings of Smith et al en Termath et al [54,55] Figure 4 showed a high probability for framework deprotonation for H-SAPO-34 loaded with 5 methanol or 8 water molecules per acid site. Although these loadings might seem relatively high, the adsorbed guest molecules are still very mobile under the simulated conditions (Supporting Information section S3).…”
Section: Proton Mobilitysupporting
confidence: 89%
See 4 more Smart Citations
“…For water, which has a lower proton affinity than methanol (697 kJ/mol vs 761 kJ/mol [77] ), higher loadings are required to obtain similar levels of proton transfer. With sufficient amounts of water, hydronium ions can be stable species, which is in correspondence with the findings of Smith et al en Termath et al [54,55] Figure 4 showed a high probability for framework deprotonation for H-SAPO-34 loaded with 5 methanol or 8 water molecules per acid site. Although these loadings might seem relatively high, the adsorbed guest molecules are still very mobile under the simulated conditions (Supporting Information section S3).…”
Section: Proton Mobilitysupporting
confidence: 89%
“…For water, which has a lower proton affinity than methanol (697 kJ/mol vs 761 kJ/mol [77] ), higher loadings are required to obtain similar levels of proton transfer. With sufficient amounts of water, hydronium ions can be stable species, which is in correspondence with the findings of Smith et al en Termath et al [54,55] (Supporting Information section S3). We selected these two most extreme situations for further analysis of proton motion as during these simulations the best sampling of proton transfer reactions was achieved.…”
Section: Proton Mobilitysupporting
confidence: 89%
See 3 more Smart Citations